2019
DOI: 10.1177/1524838018806505
|View full text |Cite
|
Sign up to set email alerts
|

Who, When, How, and Why Bystanders Intervene in Physical and Psychological Teen Dating Violence

Abstract: Teen dating violence victimization is associated with a host of adverse mental and physical health problems. A number of bystander-focused interventions have been developed to mitigate the occurrence of abuse but with varying effectiveness. There remains a need to understand more about bystander behaviors used by adolescents to ensure that existing intervention components match with bystanders’ attitudes and behaviors about intervening. The current study is a scoping review of existing literature on adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 70 publications
5
24
0
1
Order By: Relevance
“…Taken together these findings suggest that perceptions of the school environment, specifically about school personnel, are associated with adolescents’ attitudes and intended behavior. Although we cannot draw causality from our findings, this conclusion is consistent with previous research showing that school climate variables may impact students’ bystander behavior (Debnam & Mauer, 2019). The current study goes beyond other research on peer norms (Beckmann et al, 2019) to an understanding of the important role of school staff for SDV norms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taken together these findings suggest that perceptions of the school environment, specifically about school personnel, are associated with adolescents’ attitudes and intended behavior. Although we cannot draw causality from our findings, this conclusion is consistent with previous research showing that school climate variables may impact students’ bystander behavior (Debnam & Mauer, 2019). The current study goes beyond other research on peer norms (Beckmann et al, 2019) to an understanding of the important role of school staff for SDV norms.…”
Section: Discussionsupporting
confidence: 92%
“…Adolescents tend to intervene in situations of SDV when they have a supportive relationship with school staff and can be hindered from helping by school climate variables such as perceptions that schools do not take student dating violence seriously (Debnam & Mauer, 2019). Debnam and Maurer also discuss the importance of adolescents' perceptions of school personnel' intentions to intervene.…”
Section: Social Norms Attitudes and Bystander Behaviormentioning
confidence: 99%
“…These interventions have targeted both the general young population and youth at risk of suffering from or committing gender violence like children exposed to domestic violence, or witnesses of maternal abuse. Most interventions have been focused on increasing knowledge of violence and traditional gender roles [ 24 ], in addition to providing skills that allow young people to confront frustration and resolve conflicts in a non-violent way [ 22 ], and increasing awareness and skills about appropriate bystander interventions among adolescents [ 25 , 26 ]. Although the evaluations of these interventions are heterogeneous, the results show that it is possible to reduce victimization and perpetration of dating violence [ 23 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (predominantly in the United States) have examined the ways in which friends respond to IPV and the factors associated with their responses. They have found that when friends witness or notice IPV, they report offering help to the victim or confronting the abuser (Casey et al, 2018; Debnam & Mauer, 2019). For example, Fry et al (2014) surveyed 1,312 U.S. high-school students (of which 22% had a friend in an abusive relationship) and found that 79% had talked to the friend and 80% had told their friend to leave the relationship.…”
Section: Friends’ Responses To Young Women’s Experiences Of Ipvmentioning
confidence: 99%